Migration Patterns of Tundra Birds: Tracking Radar Observations along the Northeast Passage - Alerstam, Thomas; Gudmundsson, Gudmundur A. (ARCTIC, 1999)
Bird migration was recorded by tracking radar and visual observations at 15 study sites, situated between 50°E and 170°E along the Northeast Passage, during a ship-based expedition in July and August 1994. A total of 1087 radar tracks (average duration 220 s) of bird flocks on postbreeding migration were recorded. Migration was dominated by waders and to a certain degree also skuas (especially pomarine skua Stercorarius pomarinus). Terns, gulls, ducks, and geese were also among the migrants tracked by radar. The radar data revealed a major migratory divide at about 100°E (Taymyr Peninsula), with mainly eastbound migration to the east of this divide, and mainly westbound migration to the west of it. The main stream of eastbound migration was directed toward the sector 90-120° and that of westbound migration toward the sector 240-270°; these directions are broadly in parallel with the coasts of the Arctic Ocean east and west of the Taymyr Peninsula, respectively. There was also important ENE migration, which provided strong indications of long-distance flights along orthodrome-like routes directly between Siberia and North America, across vast expanses of the Arctic Ocean pack ice. Analysis of flight directions in relation to wind indicated complete compensation for wind drift. Mean flight altitude was 1.3 km, and the birds regularly travelled at high altitudes above 3 km (9% of the tracks) up to a maximum height of 4.8 km. They preferred to migrate on occasions and at altitudes with following winds; such conditions provided an average gain in speed of 4.6 m/s. There were also recurrent cases of birds migrating in tailwinds of gale force, between 18 and 24 m/s. The birds' airspeed varied between 8 and 22 m/s, with a mean of 14 m/s. Airspeed was significantly correlated with altitude, wind, and vertical speed and seemed to be intermediate between the speeds for minimum power and maximum range predicted by aerodynamic theory. Durant une expédition ayant pour base un navire, réalisée en juillet et août 1994, on a ...